Place branding in the metaverse - Santos, Ana Gil Gama dos (2024)
The present dissertation investigates the strategic utilization of the metaverse in shaping the place branding of global cities, focusing on the case studies of Seoul, South Korea, and Dubai, United Arab Emirates. The study uses a qualitative research design, case study methodology, and content analysis to examine the metaverse methods employed by these cities. The research attempts to understand the impact of metaverse activities on city branding by combining empirical data with insights acquired from a thorough literature review. The analysis reveals that both Seoul and Dubai strategically leverage the metaverse to enhance their place branding strategy. Seoul, has adopted the metaverse Seoul project, which includes virtual experiences and events that expand its brand identity into the digital domain. The project highlights Seoul's cultural richness and promotes worldwide involvement through immersive virtual tourism and interactive cultural events. Dubai, on the other hand, pursues a distinct decentralized metaverse strategy, promoting itself as a pioneer in the adoption of innovative technology. The "Dubai Metaverse Strategy" emphasizes collaboration, variety, and economic growth in the virtual sphere. Moreover, Dubai promotes the development of a virtual economy, focusing on blockchain technology to protect transactions and ownership. The metaverse serves as a platform for Dubai to promote its cultural heritage, provide virtual tourism experiences, and stimulate economic growth through digital goods and services. The integration of empirical findings and a literature review highlights similarities and differences between the two cities, emphasizing the importance of innovation, diversified target audience involvement, and multi-channel communication in metaverse-driven place branding. The study underlines the metaverse's economic possibilities, including possibilities for entrepreneurship, employment development, and worldwide accessibility. While the study contributes to our understanding of the metaverse's impact on place branding, it recognizes limitations such as the dynamic nature of the metaverse environment and the case study's specificity. The dissertation concludes with managerial implications, emphasizing actionable insights from the research and proposing avenues for future research, such as longitudinal studies, more diverse case selections, and in-depth assessments of internal organizational changes and ethical considerations in metaverse strategies.